Assessment of Eutrophication Abatement Scenarios for the Baltic Sea by Multi-Model Ensemble Simulations - Meier, H. E. Markus; Edman, Moa K.; Eilola, Kari J.; Placke, Manja; Neumann, Thomas; Andersson, Helén C.; Brunnabend, Sandra-Esther; Dieterich, Christian; Frauen, Claudia; Friedland, René; Gröger, Matthias; Gustafsson, Bo G.; et al. (Frontiers in Marine Science, 2018)
To assess the impact of the implementation of the Baltic Sea Action Plan (BSAP) on the future environmental status of the Baltic Sea, already available uncoordinated multi-model ensemble simulations for the Baltic Sea region for the 21st century were analyzed. The scenario simulations were driven by regionalized global general circulation model (GCM) data using several regional climate system models and forced by various future greenhouse gas emission and air- and river-borne nutrient load scenarios following either reference conditions or the BSAP. To estimate uncertainties in projections, the largest ever multi-model ensemble for the Baltic Sea comprising 58 transient simulations for the 21st century was assessed. Data from already existing simulations from different projects including regionalized GCM simulations of the third and fourth assessment reports of the Intergovernmental Panel on Climate Change based on the corresponding Coupled Model Intercomparison Projects, CMIP3 and CMIP5, were collected. Various strategies to weigh the ensemble members were tested and the results for ensemble mean changes between future and present climates are shown to be robust with respect to the chosen metric. Although (1) the model simulations during the historical period are of different quality and (2) the assumptions on nutrient load levels during present and future periods differ between models considerably, the ensemble mean changes in biogeochemical variables in the Baltic proper with respect to nutrient load reductions are similar between the entire ensemble and a subset consisting only of the most reliable simulations. Despite the large spread in projections, the implementation of the BSAP will lead to a significant improvement of the environmental status of the Baltic Sea according to both weighted and unweighted ensembles. The results emphasize the need for investigating ensembles with many members and rigorous assessments of models’ performance.